Evidence for natural hybrtidisation between the two oyster sub-species Crassostrea gigas and Crassostrea angulata in Southern Europe - Boudry, Pierre; Huvet, Arnaud; Fabioux, Caroline; Lapegue, Sylvie (34th Annual Meeting of the Populations Genetics Group, 2001)
Crassostrea angulata and Crassostrea gigas, two cupped oyster taxa of Asian origin (O'Foighil et al, 1998), were successively introduced into Europe during the XVIth and the XXth century respectively (Héral and Grizel, 1991). To date, populations presumed to be C. angulata remain only in the south of Spain and Portugal, while the geographic range of C. gigas is expending, notably due to aquaculture. The two taxa can be distinguished by RFLP analysis of the mitochondrial Cytochrome Oxydase I locus (COI). This marker revealed strong genetic differentiation between Asian populations of the two taxa (Boudry et al., 1998). In contrast, nuclear markers showed a much lower genetic differentiation (Huvet et al, in press). The absence of any reproductive barrier between these two taxa was demonstrated under experimental condition (Gaffney and Allen, 1993; Huvet et al., in prep), so hybridisation might occur in the wild. To study this phenomenon, nine populations were sampled along the Atlantic coasts of France, Spain and Portugal. Using the COI marker, less than 1% of oysters in France and northern Spain were found to be C. angulata. C. angulata was found only in the south of Portugal and Spain. Only one population, in the south of Portugal, was clearly a mixture of C. gigas and C. angulata haplotypes. A significant allele size polymorphism was observed at the CG44 microsatellite locus and allele sequences showed that this was due to the presence of an insertion. Its presence or absence was demonstrated by a PCR-RFLP method (marker CG44R). The analysis of Asian populations suggests that the specificity of the marker CG44R appeared before the introduction of the two taxa into Europe. Our results show that allele frequencies at the marker CG44R follow a pattern highly similar to that observed for COI, confirming the mixture of C. gigas and C. angulata in southern Portugal. The absence of linkage desequilibrium in this population supports the hypothesis that natural hybridisation occurs between C. gigas and C. angulata in the south of Portugal. However, such hybridisation occurs only in sites where aquaculture brings the two taxa into contact. No natural gene flow can be detected between C. gigas and C. angulata populations. Consequently, the present expansion of C. gigas aquaculture in southern Europe potentially endangers remaining populations of C. angulata.